Determinant Factors That Influence SME Owners’ Decision-Making In Choosing A Premise For Its Business - Hor, Siew Mun (2021)
Given the importance of small and medium enterprises (SMEs) is arising nowadays and becoming the drivers of economic growth in the country, business owners are paying very little attention devoted to the factors that bring either positive or negative impact to their business performance. With the paucity of research on the business premise selection from the perspective of SMEs, this study aims to identify the determinant factors that influence the SMEs decision in selecting a business premise for their business operations. Property investors or developers will be able to understand the utmost important aspects of property selection of SMEs to reduce property overhang issues, or to design and build properties that cater their requirements. The research was conducted using survey questionnaire to identify the factors that influence the SME owners’ business premise decision. This paper analyses surveys from 251 respondents who are SME owners in Malaysia, to investigate the determinant factors as a premise occupier. It is no surprise that location is always the most researched and the most influential determinant factor for organizations in selecting a property. We established a comprehensive set of factors and identify the determinant factors. As a result of the study, our findings produce a different outcome than what we have always expected. The identified factors were used to rank according to the degree of importance level. It turns out that there are other factors influencing the decisions of SME owners. The communality of the determinant factors was categorized across different real estate sectors such as office building, commercial shop lots, retail stores, residential units for commercial purposes, and industrial properties. While analysing the degree of importance of those criteria, findings demonstrated that SME owners’ main determinant factors are focusing largely on property attributes, followed by services attributes, locational attributes, affordability attributes and developer attributes.